Knowledge and Behaviour of Young People Concerning Fertility Risks – Results of a Questionnaire - Fügener, J.; Matthes, A.; Strauß, B. (Geburtshilfe und Frauenheilkunde, 2013)
Purpose: The aim of this study was, in the light of the increasing number of involuntarily childless couples, to investigate the state of knowledge of young people of fertile age about the risks for fertility disorders and their own risk behaviour. In addition, we wanted to check for a relationship between these aspects and the motives for wanting children, individual personality traits and psychological status. Materials and Methods: 498 women and men between the ages of 18 and 30 years participated in an anonymous survey. The sample consisted of 153 medical students, 190 students from other faculties and 155 vocational trainees. Their knowledge was tested by way of open questions on reproduction. The sum total from relevant life-style factors was used to estimate their risk-taking behaviour. Their psychic states were examined using the Health Questionnaire for Patients “Gesundheitsfragebogen für Patienten” PHQ-D, in addition the Leipzig Questionnaire on Motives for Wanting Children “Der Leipziger Fragebogen zu Kinderwunschmotiven” and the short version of the “Big Five Inventory” BFI-K were used. Results: The participants were aware of the risks for fertility disorders but did not always correctly assess their influence on fertility. Their knowledge about reproduction was rather low (on average 6.3 from 16 points). Medical students had a significantly higher state of knowledge and exhibited less risky behaviour as compared to the other two groups. Depressiveness and risky behaviour correlated positively and emotional aspects played the major role in attitudes towards having children. Risk behaviour was best predicted by the variables depressiveness, low level of knowledge and the feeling of being restricted in personal life by children. Discussion: Lack of knowledge on the topics fertility and reproduction could be a reason for risky behaviour and thus have a negative impact on lifestyle factors relating to fertility. Young people are aware of the risk factors that may affect fertility but do not always act accordingly. Primary prevention or, respectively, health promotion is thus necessary to prevent further increases in the number of infertile couples.
Keywords: knowledge about fertility; lifestyle; involuntary childlessness; prevention